A Educação Ambiental e a Formação de Professores - De Assis, Aiany Ruth Silva; Chaves, Manoel Rodrigues [UNESP] (My University, 2015)
Environmental issues require companies to seek new ways of thinking and acting, finding new ways that ensure the ecological sustainability. The joint work between people inside and outside the school environment lets you develop solid relationships of respect and commitment to the environment in its entirety, as well as modify the way we manage the available resources on the planet, because the natural conflicts of varying perceptions about the environment require a greater understanding of the socioeconomic interests, considering the oscillation of social inequalities. Knowledge in Geography and Biology related to Environmental Education (EE) propose the development of attitudes and relevant to relations between human beings and between them the middle values. They enable the learning process develops the construction of scientific concepts and verify the contribution of teachers in areas of Geography and Biology for Environmental Education. The research was conducted in the State College Dr. Vasco Gonçalves dos Reis in Urutaí (GO) and that way, we intend to discuss the formation of geography and biology teachers about the possibility of working with EA.
Environmental education and training of teachers
Keywords: Environmental Education; Schools; Teacher training